Fatwa Infrastructure in Indonesian Local Governance: Religious Authority, Digital Circulation, and Policy Legitimacy - Muhammad Ridho (Pen Of Political Authority and Religion, 2026)
Fatwa has become increasingly important in Indonesian local governance as religious authority circulates beyond clerical forums and enters administrative, political, and digital arenas. In decentralized settings, moral legitimacy often matters as much as formal legality, making religious reasoning an influential resource in local policymaking and public justification. This article examines how fatwa becomes politically actionable in subnational governance in Indonesia. The article adopts a qualitative and theory-driven approach informed by studies of religious authority, decentralization, digital politics, and governance infrastructure. It draws on academic literature, policy-related materials, public communication, and documented cases concerning the use of fatwa in local policy debates, administrative framing, and digitally mediated public discourse. Analytical attention is directed to governance translation, reputational signaling, digital authority markers, and local scope variation. A mechanism-based synthesis is used to explain how religious legal reasoning becomes portable, publicly persuasive, and institutionally usable across local political settings. Fatwa emerges as politically consequential when it functions as an infrastructural shortcut linking moral authority, bureaucratic routine, and public legitimacy. Religious reasoning therefore affects local governance not only through doctrine, but through its translation into administrative cues and networked communication. The article contributes to the field by offering an integrated framework for understanding how fatwa operates as infrastructure in decentralized democratic governance.